Knowledge, attitudes and opinions towards measles and the MMR vaccine across two NSW cohorts - Daniel Brieger; Matthew Edwards; Poonam Mudgil; John Whitehall (Elsevier, 2017)
Abstract Objective: Although the number of national measles cases has greatly decreased since 1980s, there has been resurgence in disease incidence in recent years. While parental knowledge and attitudes toward both disease and vaccinations are known to influence vaccine uptake, the contribution of these factors toward vaccination rates in NSW populations has not been studied. The aim of this study was to investigate the knowledge and opinions on measles and MMR vaccine in NSW Central and North Coast regions. Methods: Parents (n=201) of children <12 years were surveyed with a purpose design survey at public beaches at the Central Coast and community markets at the North Coast. Results: Eight per cent of respondents reported not immunising their child with MMR vaccine. Most respondents recognised that measles is a highly contagious disease. Non‐immunisers were found to be older, had a lower perceived severity of measles, were less likely to agree with the efficacy and safety of the vaccine, and were more likely to have encountered someone who had suffered side‐effects of the vaccine. Conclusions: There is considerable concern over safety of MMR vaccine among non‐immunisers. Implications for public health: Improving confidence in MMR vaccine should be a target of future public health interventions.